Association of the Amount and Pattern of Physical Activity With Arterial Stiffness: The Maastricht Study - Evelien J. Vandercappellen; Ronald M.A. Henry; Hans H.C.M. Savelberg; Julianne D. van der Berg; Koen D. Reesink; Nicolaas C. Schaper; Simone J.P.M. Eussen; Martien C.J.M. van Dongen; Pieter C. Dagnelie; Miranda T. Schram; Marleen M.J. van Greevenbroek; Anke Wesselius; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2020)
Background Arterial stiffness is an independent risk factor for cardiovascular disease and can be beneficially influenced by physical activity. However, it is not clear how an individual’s physical activity pattern over a week is associated with arterial stiffness. Therefore, we examined the associations of the amount and pattern of higher intensity physical activity with arterial stiffness. Methods and Results Data from the Maastricht Study (n=1699; mean age: 60±8 years, 49.4% women, 26.9% type 2 diabetes mellitus) were used. Arterial stiffness was assessed by carotid‐to‐femoral pulse wave velocity and carotid distensibility. The amount (continuous variable as h/wk) and pattern (categorical variable) of higher intensity physical activity were assessed with the activPAL3. Activity groups were: inactive (<75 min/wk), insufficiently active (75–150 min/wk), weekend warrior (>150 min/wk in ≤2 sessions), and regularly active (>150 min/wk in ≥3 sessions). In the fully adjusted model (adjusted for demographic, lifestyle, and cardiovascular risk factors), higher intensity physical activity was associated with lower carotid‐to‐femoral pulse wave velocity (amount: β = −0.05, 95% CI, −0.09 to −0.01; insufficiently active: β = −0.33, 95% CI, −0.55 to −0.11; weekend warrior: β = −0.38, 95% CI, −0.64 to −0.12; and regularly active: β = −0.46, 95% CI, −0.71 to −0.21 [reference: inactive]). These associations were stronger in those with type 2 diabetes mellitus. There was no statistically significant association between higher intensity physical activity with carotid distensibility. Conclusions Participating in higher intensity physical activity was associated with lower carotid‐to‐femoral pulse wave velocity, but there was no difference between the regularly actives and the weekend warriors. From the perspective of arterial stiffness, engaging higher intensity physical activity, regardless of the weekly pattern, may be an important strategy to reduce the risk of cardiovascular disease, particularly in individuals with type 2 diabetes mellitus.